Notas varias sobre Heliconia rodriguezii (Heliconiaceae) de Costa Rica - Morales, Carlos O. (2016)
Heliconia rodriguezii was described in 1982, but all the Costa Rican specimens were at the USJ Herbarium. Isotypes were distributed to other herbaria lately in May and June 2002. Moreover the herbarium acronyms for the isotypes are erroneously cited in the original publication. Notes on distribu- tion, ecology, and morphology of this rare, endemic, and poorly known species are given.